Energy transfer via exciton transport in quantum dot based self-assembled superstructures - Bernardo, César Rui Freitas (2016)
We fabricated dendrite-type superstructures of fractal dimension consisting of CdSe/ZnS & CdTe capped nanodots. These structures were studied using microscopic fluorescence intensity imaging as well as spectral and lifetime mapping.